Exposure to war and conflict: The individual and inherited epigenetic effects on health, with a focus on post-traumatic stress disorder - Raza, Zara; Hussain, Syeda F.; Foster, Victoria S.; Wall, Joseph; Coffey, Peter J.; Martin, John F.; Gomes, Renata S. M. (Frontiers in Epidemiology, 2023)
War and conflict are global phenomena, identified as stress-inducing triggers for epigenetic modifications. In this state-of-the-science narrative review based on systematic principles, we summarise existing data to explore the outcomes of these exposures especially in veterans, and show they may result in an increased likelihood of developing: gastrointestinal 1-4; auditory 5,6; metabolic 7; and circadian 8 issues, as well as post-traumatic stress disorder (PTSD). We also note that, despite a potential “healthy soldier effect”, both veterans and civilians with PTSD exhibit altered DNA methylation status in hypothalamic-pituitary-adrenal (HPA) axis regulatory genes such as NR3C1. Genes associated with sleep (PAX8; LHX1) are seen to be differentially methylated in veterans. A limited number of studies also revealed hereditary effects of war exposure across groups: decreased cortisol levels and a heightened (sex-linked) mortality risk in offspring. Future large-scale studies further identifying heritable risks of war, as well as any potential differences between military and civilian populations, would be valuable to inform future healthcare directives.